A review on the reuse possibilities of decommissioned offshore fixed platforms for marine renewable energy applications - Syriac, Robin; Prakash, M N Senthil (Journal of Naval Architecture and Marine Engineering, 2023)
There are ever-increasing efforts on utilising non-conventional energy resources so as to reduce the global carbon footprint and reduce pollution caused by extensive use of energy from conventional sources. At the same time, the energy extraction from the abundant marine renewable energy resources available offshore need more development due to difference in the levelized cost of energy (LCOE) compared to energy extracted onshore, though the difference in the cost of energy is getting reduced faster than expected. Meanwhile hundreds of offshore platforms already existing in oil and gas industry will undergo decommissioning at the end of its life; which will require the platform to be removed or reused. In this context, the reuse possibility of such decommissioned offshore platforms to be used as support structures for marine renewable energy applications is examined. This paper presents a review on the research efforts on this topic and a discussion on the various aspects involved in the possible reuse of decommissioned offshore fixed platforms for marine renewable energy applications. Journal of Naval Architecture and Marine Engineering Vol 19(2), December, 2022 p. 71-82